Analysis of Recognition from the Perspective of International Law and Implementation of Public Policies in Indonesia and Myanmar - Ni Made Diana Kencana Putri (Focus Journal : Law Review, 2023)
Human rights are a universal issue that is of concern to the international community. The countries of Indonesia and Myanmar certainly have a historical record of quite large human rights violations, so it is very important to know and learn about the recognition of human rights between the two countries and the implementation of public policies related to human rights in these two countries, namely Indonesia and Myanmar. This study aims to analyze, discuss, and provide an overview or view of the differences in the recognition of human rights between Indonesia and Myanmar from the perspective of international law, while also analyzing the implementation of public policies related to rules and laws regarding human rights. human rights in both countries through legislative mechanisms and public policy practices, especially in Indonesia and Myanmar. The method used in this study is a normativelegal method with data analysis techniques through literature studies, collecting information from various sources, including reports from international and national human rights organizations, academic publications, journals, and other information sources related to human rights. The main findings show that there are several differences in the recognition of human rights between Indonesia and Myanmar based on international conventions on human rights.In addition, the implementation of rules or laws on human rights in both countries also has its own challenges, such as the weak protection system for victims of human rights violations and local cultural factors. The conclusion of this research is that, despite progress in implementing international standards on human rights in Indonesia and Myanmar, there are still some challenges that need to be overcome. Therefore, there is a need for further efforts from the government and civil society to increase the recognition and protection of human rights in the two countries. This research provides a deeper understanding of comparative human rights in Indonesia and Myanmar, as well as valuable insights for efforts to improve and protect human rights in both countries.